Metabolomic exploration of the physiological regulatory mechanism of the growth and metabolism characteristics of Chlorella vulgaris under photoautotrophic, mixotrophic, and heterotrophic cultivation conditions. (June 2023) - Cao, Yueqin; Yang, Shuling; Wang, Juhua; Kong, Weibao; Guo, Baomin; Xi, Yuqin; Zhang, Aimei; Yue, Bin
Abstract: Microalgae have various trophic modes such as photoautotrophy, mixotrophy, and heterotrophy, and the physiological and metabolic processes of algal cells in different trophic modes are different. To explore the mechanism underlying trophic mode-mediated regulation of the physiological metabolism of microalgae, Chlorella vulgaris 31 was cultivated under photoautotrophic, mixotrophic, and heterotrophic conditions. Mixotrophic and heterotrophic cultivation significantly promoted the growth, biomass, and lipid and saccharide biosynthesis of C. vulgaris, while higher photosynthetic pigment and protein content could be obtained under autotrophic conditions. Flow cytometry analysis revealed that light periodically and significantly regulated agal cell growth under the photoautotrophic condition, but a weakened effect was observed under mixotrophic and heterotrophic conditions. The mitochondrial structure was affected by enhanced aerobic respiration under mixotrophic and heterotrophic modes. Moreover, the accumulation of starch grains and lipid droplets was significantly higher than that in the photoautotrophic control; however, no significant changes were observed in the chloroplast and nucleus. Intracellular metabolites in mixotrophic and heterotrophic modes varied markedly, mainly involving saccharides, organic acids, fatty acids, and amino acids. Metabolic pathway analysis indicated that mixotrophy and heterotrophy could significantly enhance glycolysis, the tricarboxylic acid cycle, and the pentose phosphate pathway on the 3rd day of cultivation, while higher acetyl-CoA levels were available for fatty acid synthesis in the stationary phase. This finding clarified the mechanism of mixotrophic and heterotrophic growth of C. vulgaris for biomass and biomolecule production. Graphical abstract: Image 1 Highlights: Growth of C. vulgaris was promoted by mixotrophic and heterotrophic cultivation. Glucose inhibited the photosynthesis of C. vulgaris but did not affect chloroplast structure. Glucose promoted the synthesis of lipid and carbohydrate but decreased protein in C. vulgaris. Trophic mode and glucose concentration affect the cell cycle of C. vulgaris. Mixotrophy and heterotrophy promote glycolysis and fatty acid biosynthesis of C. vulgaris.